Rethinking Religious Freedom to Assure Harmonisation of Inter-Religious Life in Indonesia - Mohammad Hazyar Arumbinang (Fakultas Hukum Universitas Muhammadiyah Magelang, 2021)
This article provides an in-depth analysis and a critical examination of the human rights protection instrument that does not govern the mechanism to resolve the problem of Freedom of Religion rights violation. This article use normative legal research with statutory and historical approaches. The data will be analysed by using descriptive-analytical analysis. This article reveals that Human Rights Protection, especially on the Right to Freedom of Religion, is still becoming a matter of concern for Indonesia. The right to freedom of religion or belief is a fundamental human right recognised in all the major human rights treaties. However, they are still inter-religious tensions and a lack of protection by the Indonesian Government. For example, the violence exploded in Karubaga, the capital of Tolikara district in Papua province. Dozens of stalls and houses were set on fire, which spread to a nearby mosque, reported as conducted by the members of the Christians Group. The recent incidents happened in Singkil, Aceh. In Indonesia a state with various religious diversity which recognises five religions and one thought, it still does not establish the strict protection of the freedom of religion. The law only provides the mechanism on how to resolve grave human rights violations. On the other side, the protection of the light-categorised violation still cannot be enforced. Based on this analysis, the paper offers practical recommendations and guidance for state officials to enhance the protection of all religious groups in expressing their thoughts and to assure the harmonisation of inter-religion life.